2016
DOI: 10.1007/s00392-016-1000-2
|View full text |Cite
|
Sign up to set email alerts
|

Survival after percutaneous coronary intervention for chronic total occlusion

Abstract: Successful CTO recanalization is an independent predictor for improved long-term survival. Persistent CTO lesions are associated with significantly worse survival than persistent non-occlusive coronary lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Although no randomized controlled clinical trials have examined the long‐term clinical outcomes of patients with successful CTO‐PCI using drug‐eluting stents (DESs) compared with that with failed CTO‐PCI, a number of observational studies have examined this difference . However, the results of these studies were inconclusive and even contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…Although no randomized controlled clinical trials have examined the long‐term clinical outcomes of patients with successful CTO‐PCI using drug‐eluting stents (DESs) compared with that with failed CTO‐PCI, a number of observational studies have examined this difference . However, the results of these studies were inconclusive and even contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…Second, when the study that included STEMI (<20%) patients in their cohort, the result did not significantly change. Third, when studies that included BMS (<20%) were removed, all the clinical outcomes demonstrated similar results. Lastly, when studies included single vessel disease (<20%), the results remained consistent for every outcomes.…”
Section: Resultsmentioning
confidence: 86%
“…From 14 studies, 16 522 CR (39.6%) and 25 165 IR (60.4%) patients were included. STEMI was included in 10.7% of study from Valenti et al, and 12.6% within 24 h in study by Tamburino et al MVD < 20% was reported in 3 studies, whereas DES < 20% was described in 5 studies . Study results by Wu et al and Hannon et al were reported from the same registry.…”
Section: Resultsmentioning
confidence: 99%
“…In 3 (11,13,16) of the 5 studies, C-RV was associated with reduced R-RV. In 8 (6,9-11,13-16) of the 11 studies, C-RV was associated with reduced MAC(C)E. There were a number of important issues, however, in the aforementioned studies (1,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) of C-RV versus IC-RV in DES-PCI for MV-CAD (except for AMI) (Figure 1). First, "angiographic" (successful angioplasty of all diseased lesions in the major epicardial coronary vessels and their first degree side branches) and "proximal" C-RV definitions (successful angioplasty of all diseased proximal arteries) according to a study by Kim et al (18) are more accurate and clinically relevant.…”
mentioning
confidence: 99%
“…Our systematic search using keywords including "complete" or "completeness"; "incomplete" or "culprit"; "revascularization"; and "drug-eluting" identified 14 studies (1,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) summarized in Tables 1,2. The design of all studies was a non-randomized observational study, and all but one (13) studies reported adjusted HRs for outcomes of interest in "C-RV vs. IC-RV" or "IC-RV vs. C-RV".…”
mentioning
confidence: 99%